Bounded Rational Speculative and Hedging Interaction Model in Oil and U.S. Dollar Markets - CARFÌ, David; CAMPBELL, Michael (Journal of Mathematical Economics and Finance; Vol 1 No 1 (2015): Volume I Issue 1(1) Winter 2015, 2015)
A `bounded rational' overlay is constructed for a model of an interaction between two players who speculate on oil and the U.S. dollar, subject to _nancial transaction taxes. This model also has two types of operators: a real economic subject (Air) and an investment bank (Bank). Many investment operators (banks) are also considered. Their behavior equilibrates much more quickly, as they react to the move of Air. In this sense, Air is an acting external agent (such as with an external magnetic _eld in a magnetic system), whereas the random component of the bounded rational behavior of banks is `annealed' (i.e., averaged out before Air makes its next transaction). Under certain conditions for the model, the equilibrium measure for the bank agents, after Air has played its strategy, is a Gibbs measure from statistical mechanics, as the interactions between opera- tors are that for a Potential game